New evidence of alternative migration patterns for two Mediterranean potamodromous species - Ana Sofia Rato; Carlos M. Alexandre; Sílvia Pedro; Catarina S. Mateus; Esmeralda Pereira; Ana F. Belo; Bernardo R. Quintella; Maria F. Quadrado; Ana Telhado; Carlos Batista; Pedro R. Almeida (Scientific Reports)
Abstract Iberian barbel (Luciobarbus bocagei Steindachner, 1864) and Iberian nase (Pseudochondrostoma polylepis Steindachner, 1864) are two Mediterranean potamodromous fish species known to perform annual upstream migrations to reach spring spawning grounds. In the Mondego River basin, at the Coimbra dam, migratory movement patterns and individual size structure were assessed through a video recording monitoring system installed on an upstream section of a vertical-slot fish pass. Visual census for these target species during two consecutive annual cycles (2013–2014) revealed alternative migratory patterns, with the first peak of upstream movements in autumn, for both barbel (October–November) and nase (November–December). Circadian movements of both species showed a diurnal preference, contrary to what is usually described for these species. Size structure analysis for individuals of both species showed significant intra-annual differences in the size of migrating fish. Boosted regression trees models applied to the 2013–2014 visual count data identified flow and temperature as the most influential environmental predictors, triggering both species’ movements in each direction in the study years. These results provide novel information on the timing of the migratory movements of these potamodromous fish, which can be used to adapt current management and conservation measures to the specificities of their migratory behaviour.